2015
DOI: 10.1186/s12885-015-1306-x
|View full text |Cite
|
Sign up to set email alerts
|

The end of the decline in cervical cancer mortality in Spain: trends across the period 1981–2012

Abstract: BackgroundIn Spain, cervical cancer prevention is based on opportunistic screening, due to the disease’s traditionally low incidence and mortality rates. Changes in sexual behaviour, tourism and migration have, however, modified the probability of exposure to human papilloma virus among Spaniards. This study thus sought to evaluate recent cervical cancer mortality trends in Spain.MethodsWe used annual female population figures and individual records of deaths certified as cancer of cervix, reclassifying deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…However, our study illustrated that about half of all the reported cases and a third of the mortalities occurred in women of the reproductive age (15–49 years). The increasing rates of CC at young ages (25–49 years) in SA may be associated with the high prevalence of HIV in this age group, poor health care access (including screening), decreasing age at sexual debut and prevalent teenage pregnancy . However, initiation of ART in 2004 could have accounted for a reduction in mortality rates among women aged 20–24 (AAPC = −4.5%), since HIV/AIDS is a major driver of CC in young women.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study illustrated that about half of all the reported cases and a third of the mortalities occurred in women of the reproductive age (15–49 years). The increasing rates of CC at young ages (25–49 years) in SA may be associated with the high prevalence of HIV in this age group, poor health care access (including screening), decreasing age at sexual debut and prevalent teenage pregnancy . However, initiation of ART in 2004 could have accounted for a reduction in mortality rates among women aged 20–24 (AAPC = −4.5%), since HIV/AIDS is a major driver of CC in young women.…”
Section: Discussionmentioning
confidence: 99%
“…Em Espanha foram reportados resultados semelhantes. 28 O exame citológico para deteção de CCU tem forte impacto na redução da mortalidade devido a esta forma de neoplasia. 3,7,8 Em Portugal esta forma de diagnóstico surgiu na década de 60, 29 mas foi exclusivamente utilizada para rastreios de forma oportunista durante a maior parte do período de tempo em análise.…”
Section: Discussionunclassified
“…No entanto, tal situação pode ser explicada pela não adesão a qualquer tipo de rastreio. Em Portugal, 31,32 à semelhança do observado em Espanha, 28 tem sido demonstrada uma menor prevalência de adesão ao exame citológico cervical em mulheres de idade mais avançada em comparação com as mais jovens.…”
Section: Discussionunclassified
“…7 A similar reallocation method has been applied for correcting the reported mortality for cervix and corpus uteri in all the European Union member states, 8,9 as well as revealing a rapidly increasing corpus uteri mortality trend in Korea, 10 and a halt in decreasing cervix uteri cancer mortality in Spain. 11 In this paper we present the corrected figures on mortality from and incidence of cervix and corpus uteri cancers in the Nordic countries for the years 1960-2016 by using reallocation of U-NOS deaths and cases. To further validate the accuracy of reallocation, we analyzed how well the reallocation captures the changes occurring as the results of a transition in cause of death coding in Norway from 2005 onwards.…”
Section: Introductionmentioning
confidence: 99%